Pengaruh NIM, NPL, CAR, Dan BOPO Terhadap Profitabilitas Perusahaan Perbankan Di Indonesia - Brenda Nathania; Liana Susanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the effect of Net Interest Margin (NIM), Non-Performing Loan (NPL), Capital Adequacy Ratio (CAR), and Operational Expenses to Operational Income (BOPO) on the profitability of banking companies. The object of this research consists of banking sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The sample was selected using a purposive sampling method, resulting in a total of 86 datas with 30 companies. The data were processed using multiple linear regression analysis with the assistance of SPSS (Statistical Product and Service Solution) version 25 and Microsoft Excel 2019. The findings indicate that NIM has a positive and significant effect on profitability, NPL has no significant effect on profitability, CAR and BOPO has a negative and significant effect on profitability. These results imply that banks must optimize their productive assets and enhance operational efficiency to maintain and improve profitability performance, which in turn may provide a positive signal to investors in making investment decisions.